(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In this article, the influence of separation blanks exposed to fiber in the process of separating cotton from the carrier air on the initial indicators of product quality is studied. A theoretical analysis based on existing patterns was carried out on it. In real conditions, theoretical studies of the problems of transferring existing technology to pneumatic transport and their practical solutions have been carried out. Conclusions and suggestions based on the results of theoretical studies of the effect of separation of cotton from air on the process are given.